Recent advances in modeling of polymer melt rheology - Wagner, M. H.; Rolón-Garrido, V. H. (Polimery, 2015)
To understand the link between polymerisation of aspecific monomer and the product properties, it is extremely helpful to perform arheological characterization under conditions as close as possible to those occuring in industry. Areliable rheological constitutive equation with as less free parameters as possible is also extremely necessary to reproduce accurately the experimental results obtained for abroad variety of polymer samples at different types of deformations. This allows the establishment of quantitative structure-property relations and permits simulations for specific polymer processes by numerical methods. It is the main objective of the present work to stress the role of rheology in melt processing in the framework of the rheotens experiment, and to give an overview about recent advances in modeling of polymer melt rheology. We discuss grandmastercurves obtained from the rheotens curves, as well as the rupture stress of polymer melts. In the context of rheological constitutive equations, we remind of the limitations of the rubber like-liquid and Doi-Edwards models. The introduction of the interchain tube pressure concept into the molecular stress function (MSF) model is explained. This approach permits to describe quantitatively the transient and steady-state uniaxial viscosities as well as the shear flow response of different nearly monodisperse linear polymers, without any free parameter.